Trans‐homophilic interaction of CADM1 promotes organ infiltration of T‐cell lymphoma by adhesion to vascular endothelium. Issue 5 (8th March 2022) - Kasai, Yutaka; Gan, Siew Pey; Funaki, Toko; Ohashi‐Kumagai, Yuki; Tominaga, Mizuki; Shiu, Shu‐Jen; Suzuki, Daisuke; Matsubara, Daisuke; Sakamoto, Takeharu; Sakurai‐Yageta, Mika; Ito, Takeshi; Murakami, Yoshinori
Abstract: The initial step of organ infiltration of malignant cells is the interaction with host vascular endothelial cells, which is often mediated by specific combinations of cell adhesion molecules. Cell adhesion molecule 1 (CADM1) is overexpressed in adult T‐cell leukemia/lymphoma (ATL) and provides a cell‐surface diagnostic marker. CADM1 promotes the adhesion of ATL cells to vascular endothelial cells and multiple organ infiltration in mice. However, its binding partner on host cells has not yet been identified. In this study, we show that CADM1 promotes transendothelial migration of ATL cells in addition to the adhesion to vascular endothelial cells. Moreover, CADM1 enhances liver infiltration of mouse T‐cell lymphoma cells, EL4, after tail vein injection, whereas a CADM1 mutant lacking adhesive activity did not. Among the known CADM1‐binding proteins expressed in primary endothelial cells, only CADM1 and CADM4 could induce morphological extension of ATL cells when plated onto glass coated with these proteins. Furthermore, CADM1‐mediated liver infiltration of EL4 cells was canceled in conventional and vascular endothelium‐specific Cadm1  knockout mice, whereas it was not canceled in Cadm4  knockout mice. These results suggest that CADM1 on host vascular endothelial cells is required for organ infiltration of ATL and other T‐cell lymphomas expressing CADM1. Abstract : Trans ‐homophilic interaction CADM1 between T‐lymphoma cells and host vascular endothelial cells is required for organ infiltration of lymphoma cells expressing CADM1.